Feasibility Study Analysis on Bot Scheme Change (Study Case: PT XYZ) - Kartika, Danny; Aliludin, Arson (The Indonesian Journal of Business Administration, 2013)
XYZ revenue in their core business has been decreasing in the latest years because of the improvement of message delivery. Meanwhile, many property assets that XYZ has are not optimally used, so XYZ makes diversification business strategy to optimize their idle asset by partnership with the partner through business scheme such as Ã¢â‚¬Å“Build, Operate, and TransferÃ¢â‚¬Â (BOT). One of the idle property assets of XYZ in which the optimization plan needs to be changed is an idle asset in Banjarmasin, a partnership between XYZ and a partner by optimizing land of XYZ. The concept of the property was mall or shopping centre, later because of financial problem caused by monetary crisis in 2008 and the competition faced makes the revenues decreased. In 2010 the property would be changed to third star hotel concept. The main problem that will be defined in this final project is whether the property asset feasible enough financially to become into hotel, based on the financial parameters that are used in the assumptions. The method used to solve is by analyzing the main root cause of problem, analyzing property industry attractiveness with Porter Five Forces, making feasibility study analysis using discounted cash flow methods of the project, analyzing sensitivity in pessimistic, most likely, and optimistic scenarios, and by giving conclusion about the project feasibility.Ã‚Â The result of feasibility study and sensitivity analysis found out that the project is feasible for both XYZ and partner in all scenarios, except not feasible in pessimistic scenario for XYZ. The project can be implemented by making clear and precise contract and agreement so to avoid terms unclearness in the future, making renovation of interior and exterior of the building and the facilities, and by maintaining the hotel in the operation stage.Ã‚Â Key Words: feasibility study, sensitivity, asset, BOT, optimize